Dampak Subsidi Pendidikan BOS dan KIP Pada Pengeluaran Rumah Tangga Miskin dan Rumah Tangga non Miskin di Wilayah Bandung Timur - Yuanisa Mulia Hendriyani; H.R.Abdul Maqin (Jurnal Riset Mahasiswa, 2021)
This study aims to determine and analyze the impact of the education subsidy program on household expenditures for the poor and non-poor households in Babakan Sari Village, Kiaracondong District, East Bandung. The aspects analyzed are differences in people's income, food and non-food expenditures, education subsidies, education expenditures, and education subsidies to food and non-food expenditures, in the poor and non-poor communities. This study uses a primary quantitative data analysis method, from the data processing shows that there are differences in the results of expenditures for poor households with non-poor household expenditures. Through this research, it is hoped that the poor can improve the quality of their education because education has a very important role in the development of a country. For non-poor people, they should care about education by provide financial assistance to schools for the advancement of education.